Writing Animals - Baker, Timothy C. author. aut Link
VII, 239 p.
Keywords: This book surveys a broad range of contemporary texts to show how representations of human-animal relations challenge the anthropocentric nature of fiction. By looking at the relation between language and suffering in twenty-first-century fiction and drawing on a wide range of theoretical approaches, Baker suggests new opportunities for exploring the centrality of nonhuman animals in recent fiction: writing animal lives leads to new narrative structures and forms of expression. These novels destabilise assumptions about the nature of pain and vulnerability, the burden of literary inheritance, the challenge of writing the Anthropocene, and the relation between text and image. Including both well-known authors and emerging talents, from J.M. Coetzee and Karen Joy Fowler to Sarah Hall, Alexis Wright, and Max Porter, and texts from experimental fiction to work for children, Writing Animals offers an original perspective on both contemporary fiction and the field of literary animal studies.